A Symmetry and Asymmetry Investigation of the Nexus Between Environmental Sustainability, Renewable Energy, Energy Innovation, and Trade: Evidence From Environmental Kuznets Curve Hypothesis in Selected MENA Countries - Andriamahery, Anselme; Qamruzzaman, Md. (Frontiers in Energy Research, 2022)
The motivation of the study is to gauge the role of renewable energy consumption, energy innovation and total trade on environmental sustainability in selected MENA countries for the period 1980-2018 under the assumption of EKC. The study implemented several econometrical tools, including structural break unit root test, Bayer-Hacked combined cointegration test, ARDL, nonlinear ARDL, and granger causality test under error correction term. Furthermore, the study utilized Dynamic OLS, Fully modified OLS and CCE for empirical model robustness test. Variables properties test detected that all the variables are stationary after the first difference but neither exposed to stationary after the second difference. The test statistics of the combined cointegration test documented a long-run association between ES, RE, EI, and TR, which is valid for both countries concerned. Regarding EKC concern, study findings with ARDL and NARDL validated the EKC hypothesis for Tunisia and Morocco. Additionally, the standard wald test statistics revealed an asymmetric association between research units in the long and short run. For Morocco, renewable energy and energy innovation have negative. In contrast, trade has a positive association with environmental sustainability. While for Tunisia, energy innovation and renewable energy have a negative, while trade has a positive association with environmental sustainability. Finally, the direction causality test documented unidirectional causality between renewable energy and environmental sustainability, trade and environmental sustainability, but the feedback hypothesis holds between energy innovation and environmental sustainability. We can advocate for specific sectoral environmental reforms in Tunisia and Morocco and suggest continuous support to environmentally-friendly technologies by combining study findings. At the same time, reduce subsidies on non-renewable energy and implement green trade policies to help advance sustainable development.